Molecular Analysis of Pseudomonas aeruginosa Strains Isolated from Hospitalized Patients in Erbil - Al-Amin, Bushra (Iraqi Journal of Science, 2025)
A total of 10 Pseudomonas aeruginosa isolates was collected from burns and wounds patients in different Erbil hospitals.Nine of these isolates were resistant to Ampicillin, Gentamycin, Ciproflaxacin, Cephalexin, Erythomycin, and Chloramphenicol, but sensitive to Naladixic acid, Cortimoxazol and Polymexin-B. While the isolate P. E 10 is resistant to Naladixic acid in addition to above.The bacterium was found to contain two plasmid bands on agarose gel.Transformation revealed that the resistance to the antibiotics was encoded by non- conjugative plasmids while no correlation was found with virulence determinants.